Alleviation of adverse effects of nickel on growth and concentration of copper and manganese in wheat through foliar application of ascorbic acid. Issue 7 (7th June 2022) - Sabir, Muhammad; Naseem, Zainab; Ahmad, Waqar; Usman, Muhammad; Nadeem, Faisal; Saifullah,; Ahmad, Hamaad Raza
Abstract: We investigated the role of ascorbic acid (AsA) to alleviate nickel (Ni) induced adverse effects on growth and concentration of Ni, copper (Cu), and manganese (Mn) in hydroponically grown wheat varieties viz. Galaxy, Punjab-2011, and FSD-08. Plants were exposed to five levels of Ni viz. 0, 5, 10, 15, and 20 mg L −1 . After 1 week, AsA (1 mM) was sprayed onto the Ni-stressed plants. FSD-08 produced the maximum SDW with and without AsA compared to other varieties. FSD-08, Galaxy, and Punjab-2011 witnessed 2.61-, 2.83-, and 7.5-fold increases in SDW with AsA, respectively. Wheat plants contained the maximum Ni in shoots and roots with a Ni level of 20 mg L −1 irrespective of varieties. Nickel in shoots decreased with AsA witnessing 13, 12, and 10% decrease in FSD-08, Punjab-2011, and Galaxy, respectively. Nickel in roots of FSD-08 decreased by 18% while increased by 3.34-fold and 3.50-fold in Galaxy and Punjab-2011, respectively with AsA. Nickel decreased Cu in shoot and Mn in shoot and root while Cu in roots of all wheat varieties increased. It was concluded that AsA improved the growth of Ni-stressed and FSD-08 performed better by maintaining good growth and less Ni in shoots compared to other varieties. NOVELTY STATEMENT: Exploiting plant internal mechanisms with foliar application of different organic substances have widely been investigated to decrease metal accumulation and their adverse effects on plants. However, the differential response of different varieties to metal accumulation in response to foliar application of ascorbic acid is not well documented. This study was conducted to investigate the effect of exogenous application of ascorbic acid on growth response, the concentration of Ni, Cu, and Mn in three wheat varieties.